Identification and multivariable control in state space of a permanent magnet synchronous generator - Albarracín Ávila, Danna Lisseth; Padilla Buritica, Jorge Iván; Giraldo Suárez, Eduardo (TECCIENCIA, 2014)
In this paper, a scheme for online identification of multivariable systems (MIMO) and a linear state feedback control is considered. The identification algorithm takes into account the input/output behavior in order to obtain a linear state spaces model that describes adequately the system in discrete time. This representation is obtained by using an online identification method such as the projection algorithm. An optimal linear quadratic regulator is applied in discrete time, where the obtained state feedback control law minimizes the quadratic cost function to calculate the optimal gain matrix. The proposed methodology for identification and multivariable control is applied an evaluated in a wind turbine with a Permanent Magnet Synchronous Generator (PMSG).